Nano-metal oxides induce antimicrobial resistance via radical-mediated mutagenesis. (December 2018) - Zhang, Ye; Gu, April Z.; Xie, Shanshan; Li, Xiangyang; Cen, Tianyu; Li, Dan; Chen, Jianmin
Abstract: The widespread use of nanoparticles has triggered increasing concern and interest due to the adverse effects on global public health and environmental safety. Whether the presence of nano-metal oxides (NMOs) could facilitate the formation of new antimicrobial resistance genes (ARGs) via de novo mutation is largely unknown. Here, we proved that two widely used NMOs could significantly improve the mutation frequencies of CIP- and CHL-resistant E. coli isolates; however, the corresponding metal ions have weaker effects. Distinct concentration-dependent increases of 1.0–14.2 and 1.1–456.3 folds were observed in the resistance mutations after treatment with 0.16–100 mg/L nano-Al2 O3 and 0.16–500 mg/L nano-ZnO, respectively, compared with those in the control. The resistant mutants showed resistance to multiple antibiotics and hereditary stability after sub-culturing for 5 days. We also explored the mechanism underlying the induction of antimicrobial resistance by NMOs. Whole-genome sequencing analysis showed that the mutated genes correlated with mono- and multidrug resistance, as well as undetected resistance to antibiotics. Furthermore, NMOs significantly promoted intracellular reactive oxygen species (ROS), which would lead to oxidative DNA damage and an error-prone SOS response, and consequently, mutation rates were enhanced. Our findings indicate that NMOs could accelerate the mutagenesis of multiple-antibiotic resistance and expanded the understanding of the mechanisms in nanoparticle-induced resistance, which may be significant for guiding the production and application of nanoparticles. Graphical abstract: Highlights: NMOs can improve the mutation frequencies of CIP- and CHL-resistant E. coli isolates. NMOs can facilitate the formation of new ARGs via de novo mutation. Resistant mutants showed resistance to multiple antibiotics and hereditary stability. Mutated genes correlated with mono- and multidrug resistance. NMOs induce intracellular ROS, oxidative DNA damage and an error-prone SOS response.